SISTEMATIKA PENULISAN KARYA ILMIAH DALAM PENELITIAN AKADEMIK - Rukiyah, Rukiyah; Hayadi, B. Herawan; Ma’arif, Tubagus Mahar; Salbiah, Siti; Ningsih, Devi Sri Cahya; Fitriani, Pina (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Scientific writing is a form of academic communication used to disseminate research findings, ideas, and scholarly studies to the academic community. The preparation of scientific papers must follow systematic scientific principles to ensure that the information presented is clear, logical, and academically accountable. This study aims to analyze the structure of scientific writing in academic research and explain the function of each section in a scientific article. The research method used in this study is a literature review by examining various scientific sources, including national and international journals, academic books, and relevant research articles. The results indicate that the structure of scientific writing generally consists of several main sections: title, abstract, introduction, literature review, research methodology, results, discussion, conclusion, and references. These sections help present research information in a systematic and logical manner, making it easier for readers to understand the research findings. Understanding the systematic structure of scientific writing is essential for students and researchers to produce high-quality scientific papers that meet academic and publication standards.